2017
DOI: 10.3233/thc-171307
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of urine flow through the side holes of a double J stent in a ureteral stenosis

Abstract: Ureteral stenosis presents with a narrowing in the ureter, due to an intrinsic or extrinsic ureteral disease, such as ureter cancer or retroperitoneal fibrosis. The placement of a double J stent in the upper urinary system is one of the most common treatments of ureteral stenosis, along with the insertion of a percutaneous nephrostomy tube into the renal pelvis. The effect that the side holes in a double J stent have on urine flow has been evaluated in a few studies using straight ureter models. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
5
11
0
Order By: Relevance
“…Notably, previous studies suggested that a large proportion of side-holes in ureteric stents made an insignificant contribution to inter-compartmental flow exchange and may thus be obstructed by crystalline deposits 17,39 . These findings were further corroborated by recent numerical studies by Kim et al ., 40,41 where the ureter architecture was reconstructed from two-dimensional axial computed tomography (CT) data collected from 19 men. It should however be noted that these prior studies were conducted on ureter models with a fixed cross-sectional area, which did not replicate the compliant nature of the ureter wall nor the presence of physiological ureteric constrictions.…”
Section: Resultssupporting
confidence: 54%
“…Notably, previous studies suggested that a large proportion of side-holes in ureteric stents made an insignificant contribution to inter-compartmental flow exchange and may thus be obstructed by crystalline deposits 17,39 . These findings were further corroborated by recent numerical studies by Kim et al ., 40,41 where the ureter architecture was reconstructed from two-dimensional axial computed tomography (CT) data collected from 19 men. It should however be noted that these prior studies were conducted on ureter models with a fixed cross-sectional area, which did not replicate the compliant nature of the ureter wall nor the presence of physiological ureteric constrictions.…”
Section: Resultssupporting
confidence: 54%
“…The total flow rates in the 5 Fr DJSs are larger than those in the other sizes, and overall, the total flow rates decrease as the DJS size increases. This result verifies one of our previous CFD simulation studies, which also showed that bigger stents result in a smaller urine flow in normal or stenotic ureters and that they are not favorable in achieving sufficient urine flow . Here, the finding was again realized, although there are some differences in models and stents between the two studies.…”
Section: Resultssupporting
confidence: 89%
“…Urine flow through the stented ureter consists of luminal and extraluminal flows, and according to previous reports, extraluminal flow plays a significant role in achieving sufficient urine flow through the stented ureter. In previous studies, we used curved and straight models of stented ureters and evaluated the total, luminal, and extraluminal flow rates and flow patterns around the stent using CFD. In particular, one of our previous studies evaluated if a larger DJS, which enables a larger luminal flow, was better for achieving satisfactory urine flow under ureteral stenosis .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance drainage, and preserve drainage under the circumstances of stone and adjacent tumor, some stent designs include holes along the length; these are typically ~1 mm in diameter, spaced 10 mm apart from each other and rotated by 90° hole-to-hole. The benefits of such side holes in commercial polymeric stents due to extraluminal flow, which is complementary to intraluminal flow, has been quantified in both in vivo and in vitro studies, and complemented with numerical simulations [14][15][16][17][18]. These studies also confirmed Poiseuille flow, thus laminar flow, through the long and narrow lumen of the stent.…”
Section: Introductionmentioning
confidence: 88%